Contributions of psychology to the nature of man - Alvites R., Julio (2015)
The article is about how to conceptualize the human individual from the psychological currents, through the history of psychology. Whereas, the way we see the human individual, for each current was different, so there were many subjects of this science as it appeared currents. We finished our psychological position to pose article and our idea of the essence of man.